Studi Deskriptif Motif Kerawang Gayo Aceh Tengah pada Baju Pengantin Adat Gayo - Fitri Rezeqi; Misgiya Misgiya (MAVIS : Jurnal Desain Komunikasi Visual, 2021)
Kerawang Gayo is the designation of the Gayo carving motifs of Central Aceh Province. The Gayo Kerawang motif can be found on wooden houses, pottery, wicker, metal, and cloth. In this context discusses the Gayo Kerawang which is applied to traditional Gayo clothes, especially wedding clothes. On the Gayo wedding dress which is still pure from the ancestors and has not been exposed to modernization, it uses a black base color (cloth) with red, green, white, and yellow thread embroidery. Whereas in the modern version of the traditional Gayo traditional wedding dress, there have been many changes both from the color of the fabric used, as well as to the shape and size of the openwork motifs used. This study aims to determine the shape, color and placement of the Gayo Kerawang motif on the traditional Gayo wedding dress. This study uses a qualitative descriptive method approach, namely by describing each object to be studied. The findings of this study indicate that eight Kerawang Gayo motifs were found on the traditional Kerawang Gayo bridal dress in Central Aceh. Namely: pucuk ni tuwis, emun berangkat, jang/peger, sarak opat, tekukur, keleton senye, emun beriring, and emun singah modification. There is also a change in the color of the traditional Gayo bridal kerawang cloth, and the placement of the Kerawang motif on the traditional Gayo wedding dress, has no special rules.